Outdoor Airborne Transmission of Coronavirus Among Apartments in High-Density Cities - Huang, Jianxiang; Jones, Phil; Zhang, Anqi; Hou, Shan Shan; Hang, Jian; Spengler, John D. (Frontiers in Built Environment, 2021)
The coronaviruses have inflicted health and societal crises in recent decades. Both SARS CoV-1 and 2 are suspected to spread through outdoor routes in high-density cities, infecting residents in apartments on separate floors or in different buildings in many super-spreading events, often in the absence of close personal contact. The viability of such mode of transmission is disputed in the research literature, and there is little evidence on the dose-response relationship at the apartment level. This paper describes a study to examine the viability of outdoor airborne transmission between neighboring apartments in high density cities. A first-principles model, Airborne Transmission via Outdoor Route (ATOR), was developed to simulate airborne pathogen generation, natural decay, outdoor dispersion, apartment entry, and inhalation exposure of susceptible persons in neighboring apartments. The model was partially evaluated using a smoke tracer experiment in a mock-up high density city site and cross-checking using CFD models. The ATOR model was used to retrospectively investigate the relationship between viral exposure and disease infection at an apartment level in two super-spreading events in Hong Kong: the SARS outbreak in Amoy Gardens and the COVID-19 outbreak in Luk Chuen House. Logistic regression results suggested that the predicted viral exposure was positively correlated with the probability of disease infection at apartment level for both events. Infection risks associated with the outdoor route transmission of SARS can be reduced to less than 10%, if the quanta emission rate from the primary patient is below 30 q/hr. Compared with the indoor route transmission, the outdoor route can better explain patterns of disease infection. A viral plume can spread upward and downward, driven by buoyancy forces, while also dispersing under natural wind. Fan-assistant natural ventilation in residential buildings may increase infection risks. Findings have implication for public health response to current and future pandemics and the ATOR model can serve as planning and design tool to identify the risk of airborne disease transmission in high-density cities.